Kesiagaan menghadapi bencana di Perpustakaan Kementerian “X” di Jakarta - Arnola Dewinta Hasan; Yeni Budi Rachman (Berkala Ilmu Perpustakaan dan Informasi, 2024)
Introduction. This study aims to identify disaster preparedness conducted by the Library of the Ministry of "X" through disaster preparedness standards by the International Federation of Library Associations and Institutions (IFLA). Data Collection Methods. Using a qualitative case study method, the data collection was carried out through observation, interviews, and document studies. Data analysis. Data from interviews and observations were reduced using transcripts and coding. The data was analyzed based on the five aspects of disaster management by IFLA. Results and Discussion. The results of the study show that among the five stages of IFLA disaster preparedness, almost all of the stages did not meet the standard and comprehensive manner. Based on the risk assessment, it is known that the biggest threat comes from the internal environment, one of them is library human resources. Lack of awareness of library human resources affects the absence of an optimal budget and disaster preparedness activities. Conclusion. The Ministry Library "X" in Jakarta had carried out disaster preparedness according to IFLA standards, however, it is still in the early stage.